An Integration of User Experience and Agile Software Development: A Systematic Literature Review - M. Arrasyid Rakhmadaszan; Teguh Raharjo; Ni Wayan Trisnawaty (AI Society & STMIK Indonesia, 2024)
New methods and best practices are being used to enhance the software lifecycle because of the recent expansion of the software industry. Agile development approaches have also been widely used, and they have positively affected people's lives and the operations of enterprises. Although agility makes working with developers easier, it does not offer enough chances to collaborate with users. In early Agile formulations, User Experience (UX) was not recognized as a distinct part of software development. The tricky part is figuring out where to integrate them and how to merge them so that the two parts interact. Combining user experience with Agile approaches is the subject of this research's proposed systematic literature review (SLR). This research found ten relevant studies highlighting the growing interest and research in merging these two critical areas of software engineering. In conclusion, this research found some papers or studies integrating user experience into Agile methodologies. Many techniques are used, and all studies have different approaches to integrate them.